Water photodissociation in free ice nanoparticles at 243 nm and 193 nm - Poterya, Viktoriya; Fárník, Michal; Oncák, Milan; Slavícek, Petr (Physical chemistry chemical physics, 2008)
The photolysis of (H(2)O)(n) nanoparticles of various mean sizes between 85 and 670 has been studied in a molecular beam experiment. At the dissociation wavelength 243 nm (5.10 eV), a two-photon absorption leads to H-atom production. The measured kinetic energy distributions of H-fragments exhibit a peak of slow fragments below 0.4 eV with maximum at approximately 0.05 eV, and a tail of faster fragments extending to 1.5 eV. The dependence on the cluster size suggests that the former fragments originate from the photodissociation of an H(2)O molecule in the cluster interior leading to the H-fragment caging and eventually generation of a hydronium H(3)O molecule. The photolysis of surface molecules yields the faster fragments. At 193 nm (6.42 eV) a single photon process leads to a small signal from molecules directly photolyzed on the cluster surface. The two photon processes at this wavelength may lead to cluster ionization competing with its photodissociation, as suggested by the lack of H-fragment signal increase. The experimental findings are complemented by theoretical calculations.